New German Dance Studies - Ruprecht, Lucia, 1972-; Manning, Susan (Book collections on Project MUSE., 2012)
New German Dance Studies offers fresh histories and theoretical inquiries that resonate across fields of the humanities. Sixteen essays range from eighteenth-century theater dance to popular contemporary dances in global circulation. In an exquisite trans-Atlantic dialogue that demonstrates the complexity and multilayered history of German dance, American and European scholars and artists elaborate on definitive performers and choreography, focusing on three major thematic areas: Weimar culture and its afterlife, the German Democratic Republic, and recent conceptual trends in theater dance._x000B__x000B_Contributors are Maaike Bleeker, Franz Anton Cramer, Kate Elswit, Susanne Franco, Susan Funkenstein, Jens Richard Giersdorf, Yvonne Hardt, Sabine Huschka, Claudia Jeschke, Marion Kant, Gabriele Klein, Karen Mozingo, Tresa Randall, Gerald Siegmund, and Christina Thurner.